2001
DOI: 10.1002/app.1604.abs
|View full text |Cite
|
Sign up to set email alerts
|

Miniemulsion copolymerization of n‐butyl methacrylate with crosslinking monomers

Abstract: Miniemulsion copolymerization of n-butyl methacrylate and crosslinking monomers such as a macromonomer crosslinker (Mac), ethylene glycol dimethacrylate (EGDMA), or an aliphatic urethane acrylate macromonomer (AUA) was utilized to obtain crosslinked latex particles. The crosslinking monomers were added at 0.2 mol %, on the basis of the amount of n-butyl methacrylate utilized in a polymerization. The development of the gel content during the copolymerization reaction differs depending on the type of the crossli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Ghazaly et al [5] reported the miniemulsion copolymerization of n-butyl methacrylate with the various crosslinking monomers. These monomers included (a) macromonomer crosslinker (Mac) with a number average molecular weight of 3480 g /mol and polydispersity index of 1-1 to 1.2, (b) ethylene glycol dimethacrylate (EDGMA) and (c) aliphatic urethane aery la te macromonomer (AU A).…”
Section: N-butyl Methacrylate-crosslinking Monomersmentioning
confidence: 99%
“…Ghazaly et al [5] reported the miniemulsion copolymerization of n-butyl methacrylate with the various crosslinking monomers. These monomers included (a) macromonomer crosslinker (Mac) with a number average molecular weight of 3480 g /mol and polydispersity index of 1-1 to 1.2, (b) ethylene glycol dimethacrylate (EDGMA) and (c) aliphatic urethane aery la te macromonomer (AU A).…”
Section: N-butyl Methacrylate-crosslinking Monomersmentioning
confidence: 99%
“…For this reason, SaPSeP does not work if PS is replaced by the more hydrophilic PMMA. [44] El-Aasser et al [23] speculated that the gelation behavior during copolymerization of butyl methacrylate and a diacrylate macromonomer (with an aliphatic main chain) was influenced by concentration gradients within the particles arising due to the different hydrophobicities of the two monomers.…”
Section: Effect Of Interfacementioning
confidence: 99%
“…[19] On the other hand, when implementing ATRP in miniemulsion, a sufficiently hydrophobic ligand must be selected for control of the polymerization to be maintained. [3] There are several reports dealing with conventional radical crosslinking polymerization in aqueous heterogeneous systems, [20][21][22][23][24][25][26] but there is little information available with regards to specific differences between these systems and their homogeneous counterparts in terms of pendant reactivities and gel formation. This topic has however been thoroughly addressed by Tobita et al, whose theoretical and experimental work [27][28][29][30][31] on conventional radical copolymerization of mono-and divinyl compounds has revealed that the network development is entirely different in emulsion polymerization compared to bulk.…”
Section: Introductionmentioning
confidence: 99%
“…Crosslinkable macromonomers composed of ethylene-butylene aliphatic hydrophobic chains and bifunctional terminal acrylic acid moieties have been synthesized 6,7 and used as both costabilizers and crosslinking agents in the miniemulsion polymerization of n-butyl methacrylate. The most recent examples are methacryloxypropyl-terminal 8 and vinyl-terminal polysiloxanes 9 used in the dispersion polymerization of methyl methacrylate in nonpolar media.…”
Section: Introductionmentioning
confidence: 99%